Axenfeld–Rieger syndrome combined with ectropion uveae and pigment dispersion syndrome: A case report. Issue 7 (17th February 2023) - Li, Yang; Liu, Jie; Tian, Qingmei; Ma, Xianzhen; Zhao, Yuhui; Bi, Hongsheng
Abstract : Background: In January 2021, we found one case of Axenfeld–Rieger syndrome combined with pigment dispersion syndrome (PDS), and this patient additionally manifested a symptom of ectropion uveae. The co-existence of both 2 syndromes is very rare and has not been reported in any literature yet. Case presentation: A 34-year-old female truck driver presented to our institution with a dimness of vision in her right eye. The patient had obvious posterior embryotoxons at bitamporal, and peripheral anterior synechia could be visualized by the slit lamp. The dispersion of pigment granules was observed behind the cornea. The pupil was slightly shifted upwards the nose, with 360° ectropion uveae. Gonioscopy revealed pigment accumulation on the trabecular meshwork. The patient underwent cataract surgery on her right eye, during which, flaky pigmentation around the posterior capsule was observed. These signs were consistent with Axenfeld–Rieger syndrome and PDS. Conclusions: We report a rare case of Axenfeld–Rieger syndrome with PDS and uveal eversion. Although the patient did not present with glaucoma, follow-up should be noted. Besides, the correlation between these 2 syndromes needs to be demonstrated by more cases or further evidence.